Advocacy of The Ombudsman Institute for The Special Region of Yogyakarta in Completing The Complaints of Educational Problems in The Special Region of Yogyakarta - Titin Widhi Astuti (Spektrum Analisis Kebijakan Pendidikan, 2021)
This study aims to describe the Advocacy of the Ombudsman Institute for the Special Region of Yogyakarta in completing the complaints of education problems in the Special Region of Yogyakarta. This research is a descriptive study with a qualitative approach. Data validity uses triangulation of sources, techniques, and time. Data analysis techniques include data collection, data condensation, data presentation, and conclusion drawings. Research Results: (1) Complaint of Education Problems in DIY Ombudsman Institutions Mapped into a Regular Complaint (Governance of Education and School Management) and Temporary (PPDB), (2) Stages of Advocacy for DIY Ombudsman Institutions, namely the Stage of Preparation (Consultation and Clarification), Implementation Stage (Coordination, investigation, mediation), and stages of assessment (monitoring). Advocacy of DIY Ombudsman Institutions specifically for education, namely educational complaints posts. (3) Supporting factors, namely the existence of pic every education office, complete documents, cooperative attitudes, and monitoring. Inhibiting factors, namely the lack of human resources, community concerns over the impact of the report, the school's violation of the definition of donations and levies, the final product recommendations as input, and the wrong perception of the public.